Comparative Analysis of Financial Performance of Coal Energy Companies on the IDX Before and During the COVID-19 Pandemic - Nurhafidz Sutisna, Taofik; Evianti, Dessy; Rachman, Rachmawaty (Program Studi Magister Akuntansi, Direktorat Pascasarjana, Universitas Sangga Buana, 2024)
The study examines how the COVID-19 pandemic affected the financial performance of coal energy companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2021. Using a descriptive comparative method, the analysis focuses on financial data from annual reports to evaluate metrics like liquidity, solvency, activity, and profitability. The findings suggest that overall, there were minimal alterations in financial performance indicators before and during the pandemic, except for noticeable variations in the cash ratio and total asset turnover ratio.